A crise civilizatória do capital, a América Latina e o Serviço Social - Firmiano, Frederico Daia [UNESP]; Silva, José Fernando Siqueira Da [UNESP]; Sant’ana, Raquel Santos [UNESP] (Cortez Editora Ltda, 2024)
This article offers elements for the analysis of the society of capital in the current stage of capitalist accumulation, as well as a debate on the ongoing structural and civilizational crisis and its particular expressions in Latin America. Supported by contributions offered by the Marxist tradition, the text emphasizes the importance of anti-capitalist resistance, as a critique of capital and capitalist society, as well as valuing the historical-critical approach in Social Work.

Este artigo oferece elementos para a análise da sociedade do capital no atual estágio de acumulação capitalista, bem como debate a crise estrutural e civilizatória em curso e suas expressões particulares na América Latina. Sustentado em aportes oferecidos pela tradição marxista, o texto ressalta a importância das resistências anticapitalistas, como crítica ao capital e à sociedade capitalista, bem como valoriza a abordagem histórico-crítica no Serviço Social.
The civilizational crisis of capital, Latin America and Social Work
Keywords: Capital crisis; Resistances; Latin America; Social Work; Crise do capital; Resistências; América Latina; Serviço Social